ASAL USUL DAN PERKEMBANGAN LEMBAGA DAKWAH ISLAM INDONESIA (L D I I) - Ottoman Ottoman (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2014)
Abstract: Emergence and development of religious streams flowing like a flood that bring negative effects to the understanding of the people of Islam itself, even it mixed reactions to the unrest in the community as a result of the intensity of the propaganda being waged as well as its development, which is so massive, such as the public reaction to the spiritualism of Ahmadiyah, but it not happened with religious beliefs, which this one, namely the Indonesian Islamic Propagation Institute (Lembaga Dakwah Islam Indonesia - LDII). This spiritualism has long historical roots in Indonesia, once banned but has not dampen the pace to continue to exist and flapping his message. Through dynamics an time was running that occur in the body of the current on this one, then its existence has gained a place in the midst of today's society. This paper will reveal about the nature of LDII, which includes the origin of the spiritualism, the names are used, the development of the spiritualism, the principal teachings developed his religious and social behavior, as well as some comments about LDII figures. Keywords: The development, LDII, Principles of thought.